A study on the chain propagation of benzoxazine. Issue 4 (8th December 2015) - Wang, Hongyuan; Zhu, Rongqi; Yang, Po; Gu, Yi
Abstract : Variation of T g with conversion of step polymerization, living chain polymerization and non-living chain polymerization of benzoxazine during the curing process. Abstract : The chain propagations of Bisphenol A-aniline benzoxazine (defined as BA-a) polymerized by thermal induction and in the presence of various catalysts or curing agents during the curing process before gelation were investigated in this paper. DSC, gel time test and GPC were used to measure the curing behavior, number-average molecular weight ( M̄ n ), glass transition temperature ( T g ), gel time ( t gel ) and curing conversion ( α ) of different benzoxazine systems. By comparing the experimental results ( M̄ n and T g ) with the models of step polymerizations and chain polymerizations proposed by Flory et al., three kinds of chain propagations of benzoxazine were observed and confirmed. The step polymerization occurred in the thermal induction or in the presence of catalyst N, N -dibenzylaniline (tAm), and then the non-living chain polymerization and the living chain polymerization occurred, respectively, when indole (Id) and other additives such as phenol (tBp), acid (HA), imidazole (IMZ) etc. were added to benzoxazine as catalysts or curing agents. Moreover, the relationship between the chain propagation and curing kinetics of benzoxazine was also established. The chain propagation of benzoxazine systems involves step polymerization, non-living chain polymerization andliving chain polymerization, the conversion of the gel point ( α gel ) is almost equal to, less than and greater than the value of the conversion at which the polymerization rate reaches a maximum ( α max ), respectively. The results may contribute to a better understanding of the polymerization mechanism of benzoxazine and provide new approaches to effective control of the polymerization kinetics and growth crosslink structures of benzoxazine.